Structural changes in Scottish ICT manufacturing sector 2001?2003: the impact on Research and Development. (2nd December 2011) - McDonald, Sean M.; McPherson, Alistair H.
The paper identifies changes in the structure of the Information & Communications Technology (ICT) manufacturing sector in Scotland, with specific reference to the major closures and redundancies during the period 2001?2003, and examines the implications of these changes for the development of the Scottish knowledge economy. However, the economic outputs of the sector, as measured by GVA, has been less severely affected and changes in the scale, composition and character of industry R&D, suggest that the indirect contribution of the sector to the development of a knowledge economy are likely to be more prevalent than in the past.